PERUBAHAN BUDAYA JAKARTA: LUNTURNYA NILAI-NILAI KESENIAN ONDEL-ONDEL BETAWI DI ERA GLOBALISASI - Herdin Muhtarom; Ilham Arsandi; Dora Kurniasih; Nida Widia; Sulaeman Sulaeman (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
The times, especially in globalization era, will have an impact, one of which is on cultural changes in Indonesia. Similarly, the change occurs in Jakarta's culture, particularly Jakarta Ondel-ondel art which has changed in the term of its values​​. This research is intended to find out related cultural changes occurring in Jakarta, especially in Ondel-ondel art, in which the values of the ondel-ondel art begins to fade gradually due to deviations in the use of ondel-ondel in globalization era as a means of earning living through busking. In this study, we used a qualitative research approach through the library research method. The results of study indicate that in globalization era era, Jakarta people do not understand the meaning contained in the art of Ondel-ondel Jakarta, therefore a strategy is needed to maintain and develop Jakarta's Ondel-ondel art in globalization era and to restore the values ​​contained in the art.